2-Hydroxy-4-(Methylthio) Butanoic Acid Isopropyl Ester Supplementation Altered Ruminal and Cecal Bacterial Composition and Improved Growth Performance of Finishing Beef Cattle - Qin, Xiaoli; Zhang, Depeng; Qiu, Xinjun; Zhao, Kai; Zhang, Siyu; Liu, Chunlan; Lu, Lianqiang; Cui, Yafang; Shi, Changxiao; Chen, Zhiming; Hao, Rikang; Li, Yingqi; et al. (Frontiers in Nutrition, 2022)
The objective of this study was to evaluate the effects of isopropyl ester of 2-hydroxy-4-(methylthio)- butyrate acid (HMBi) on ruminal and cecal fermentation, microbial composition, nutrient digestibility, plasma biochemical parameters, and growth performance in finishing beef cattle. The experiment was conducted for 120 days by a complete randomized block design. Sixty 24-month-old Angus steers (723.9 ± 11.6 kg) were randomly assigned to one of the flowing three treatments: basal diet (the concentrate: 7.6 kg/head·d-1, the rice straw: ad libitum) supplemented with 0 g/d MetaSmart® (H0), basal diet supplemented with 15 g/d of MetaSmart® (H15), and basal diet supplemented with 30 g/d of MetaSmart® (H30). Results showed that the average daily gain (ADG) increased linearly (P = 0.004), and the feed conversion ratio (FCR) was decreased linearly (P < 0.01) with the increasing HMBi supplementation. Blood urea nitrogen (BUN) concentration was significantly decreased in the H30 group (P < 0.05) compared with H0 or H15. The ruminal pH value tended to increase linearly on day 56 with the increased HMBi supplementation. The concentrations of Ammonia-nitrogen (NH3-N), propionate, isobutyrate, butyrate, isovalerate, valerate, and total volatile fatty acid (VFA) were linearly decreased in cecum (P < 0.05). The results of Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) showed that the abundance of most pathways with significant difference was higher in rumen and lower in cecum with the H30 group compared to the H0 group, and those pathways were mainly related to the metabolism of amino acids, carbohydrates, and lipids. Correlation analysis showed that ADG was positively associated with the ratio of Firmicutes/Bacteroidetes both in rumen and cecum. Additionally, the abundances of Lachnospiraceae, Saccharofermentans, Lachnospiraceae_XPB1014_group, and Ruminococcus_1 were positively correlated with ADG and negatively correlated with FCR and BUN in rumen. In cecum, ADG was positively correlated with the abundances of Peptostreptococcaceae, Romboutsia, Ruminococcaceae_UCG-013 and Paeniclostridium, and negatively correlated with the abundances of Bacteroidaceae and Bacteroides. Overall, these results indicated that dietary supplementation of HMBi can improve the growth performance and the feed efficiency of finishing beef cattle by potentially changing bacterial community and fermentation patterns of rumen and cecum.